Lactobacillus paracasei hii01 mediated fermentation of Syzygium cumini L. Fruits: Assessment of changes in phenolic content and antioxidant capacity - Sasithorn Sirilun (2018)
© 2018 The Authors. Objective: Syzygium cumini L. fruits are reported for several pharmacological applications and winemaking. The present study was conducted to develop and analyze the phytochemical content, and antioxidant properties of lactic acid bacteria mediated fermented S. cumini fruit juice (FSJ). Methods: The pH of FSJ was measured by pH meter, and total acidity was calculated by titration method. The Folin-Ciocalteu colorimetric method was employed to assess the total phenolic content (TPC), and antioxidant properties were determined by 2, 2′-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid, ferric reducing antioxidant power, and ferrous ion-chelating assays. Results: The formula 1 and 2 displayed pH of 3.23, and 3.12, respectively, after 6 months of fermentation. The acidity of F1 and F2 was regularly increased from 0.23 to 0.55 and 0.29 to 0.53 mg lactic acid equivalent per ml sample, respectively. The TPC of FSJ was progressively increased. The F1 and F2 showed an increase in TPC from 0.94 to 1.61 and 1.05 to 1.95 mg Gallic acid equivalent per ml of sample, respectively. The Formula 1 and 2 exhibited antioxidant capacities of 1.90 and 2.06 mg Trolox equivalent antioxidant capacity per ml sample, 0.81 and 0.80 quercetin equivalent antioxidant capacity per ml sample, and 1.67 and 1.82 Vitamin-C equivalents antioxidant capacity per ml sample, respectively. Ferric reducing-antioxidant power of Formula 1 and 2, and Control 1 and 2 were 3.90, 4.29, 2.96, and 3.27 mg Fe2SO4 equivalents per ml of sample, respectively. Whereas, the chelating power of samples was not significantly changed at the end of fermentation. Conclusion: The high-quality FSJ was prepared with enhanced antioxidant capacity and phenolic compounds. The probiotic containing FSJ is an alternative functional food supplement to prevent, cure and manage several degenerative disorders. Further, clinical studies are essential to insight the functional quality of FSJ.